Recycling food leftovers in feed as opportunity to increase the sustainability of livestock production. (20th April 2021) - Pinotti, L.; Luciano, A.; Ottoboni, M.; Manoni, M.; Ferrari, L.; Marchis, D.; Tretola, M.
Abstract: With the diminishing availability of farmland, climate change and the threat of declining water resources, livestock needs to meet the growing demand for food and feed by using fewer resources. The re-use of food losses as sustainable ingredients for feed formulations could represent a promising alternative to cereal grains for both monogastrics and ruminants, increasing livestock sustainability and reducing the competition between animal and human nutrition. The acceptance of food leftover for feeding animals it is still far to be completely welcomed in several countries, where the outdated stereotypical image of the garbage used as feed is still existing. To implement this practice, a renewed image of food leftover as feed is needed, mainly disseminating the most recent findings about their properties, the new technologies applied for their production and their impact on the environment. This paper aims to disseminate a wide understanding of food losses and explores the potential benefits of using two main categories of food leftovers, namely former food products (FFPs) and bakery by-products (BBPs), as alternative feed ingredients in pig and ruminant nutrition. Several characteristics of those two categories of food losses are examined and compared to a standard diet, such as nutritional-related properties, safety, efficiency and environmental implications. The literature shows that both categories of food leftovers hold a significant nutritional value and are a sustainable alternative to traditional feed ingredients. They resulted as a low risk category for animal health. In addition, when used in complete feed to replace traditional feed ingredients, neither FFPs nor BBPs do not decrease animal's growth performances. These findings valorize food losses into animal feed as a well-suited strategy to contribute to a reduced environmental and climate footprint of animal products and food waste prevention. However, a greater participation by feed/food processors and stakeholders is crucial to allow the sector to increase its contribution in the entire EU food and feed chain. Graphical abstract: Image 1 Highlights: Food leftovers can contribute to the environmental sustainability of livestock. Food leftovers like FFPs and BBPs have a high potential as animal feed. FFPs and BBPs are nutritious, highly digestible and safe feed ingredients. Food leftovers are suitable for monogastrics and ruminants' diets.